Photocatalytic degradation of two different types of dyes by synthesized La/Bi2WO6. Issue 89 (9th September 2016) - Wang, Chunying; Zhu, Qingjiang; Gu, Chuantao; Luo, Xianping; Yu, Changlin; Wu, Min
Abstract : Parameters, such as inorganic ions and pH have different effects on the photocatalytic removal of X-3B and RhB using La/Bi2 WO6 . Abstract : A lanthanum doped Bi2 WO6 composite (La/Bi2 WO6 ) was prepared using a simple hydrothermal method. The synthesized samples were well characterized using XRD, SEM, TEM, UV-vis DRS, XPS, and BET analysis methods. The photocatalytic activities of La/Bi2 WO6 on reactive brilliant red X-3B (X-3B) and rhodamine B (RhB), under simulated solar irradiation, were systematically investigated. As a result, the doped Bi2 WO6 samples possessed a higher specific surface area than pure Bi2 WO6, but still retained the crystalline phases, morphology and visible light absorption properties of pure Bi2 WO6 . The initial concentrations of dyes, the dosage of catalyst and H2 O2 all displayed the same effects on the degradation of the two dyes. However, pH showed different effects on X-3B and RhB because X-3B is an anionic dye while RhB is a cationic dye. Moreover, among all the inorganic ions studied (Na +, K +, Ca 2+, Mg 2+, NO3 −, HCO3 −, Cl −, SO4 2− ), the addition of Cl − significantly affected the adsorption and degradation of the two dyes; Cl − inhibited the total removal efficiency of X-3B, but enhanced the removal efficiency of RhB. The effects of inorganic cations were attributed to the effect of Cl − because the four metal ions were used as their chloride salts.